A comparative study on mechanical, physico-chemical, and thermal properties of rubber and walnut seed shell reinforced epoxy composites and prominent timber species. (March 2023) - Das Lala, Sumit; Deb, Payel; Barua, Emon; Deoghare, Ashish B; Chatterjee, Sushovan
Natural fillers due to their low density, light weight, abundant availability, easy processability and biodegradability have emerged as promising reinforcement in the polymer matrix. The present study explores the use of finely powdered waste Rubber seed shell (RSS) and Walnut shell (WNS) as reinforcements in the epoxy matrix Lapox B11 to develop composite material using stir casting process. The composition of filler is varied by 5, 10, 15, and 20 wt.%. The developed composites are characterized for investigating the mechanical, physico-chemical and thermal properties. An improvement in the tensile, compression, hardness and water absorption properties is observed for RSS reinforced composite compared to WNS composite. But the flexural and thermal properties are found to be better for WNS reinforced composite. Both the composites with superior properties are further compared with the properties of some prominent timbers listed in standard IS 883 1994 structural timber codes based on their availability in north-eastern (NE) region of India. The properties of both composites are found to be significantly better than the properties of the listed timber specimens. An increase in tensile strength by 123% and 72% for RSS and WNS composite is observed as compared to Sundari wood specimen. There is also an increase in compressive strength by 792% and 722% for RSS and WNS composite as compared to Sundari wood specimen. The study explores the potential of walnut shell and rubber seed shell composite as a probable replacement against conventional wooden products.